ANO1-downregulation induced by schisandrathera D: a novel therapeutic target for the treatment of prostate and oral cancers - Park, SeonJu; Das, Raju; Nhiem, Nguyen Xuan; Jeong, Sung Baek; Kim, Minuk; Kim, Dongguk; Oh, Hye In; Cho, Su-Hyeon; Kwon, Oh-Bin; Choi, Jae-Hyeog; Park, Chul Soon; Kim, Song-Rae; et al. (Frontiers in Pharmacology, 2023)
Anoctamin 1 (ANO1), a drug target for various cancers, including prostate and oral cancers, is an intracellular calcium-activated chloride ion channel that plays various physiopathological roles, especially in the induction of cancer growth and metastasis. In this study, we tested a novel compound isolated from Schisandra sphenanthera, known as schisandrathera D, for its inhibitory effect on ANO1. Schisandrathera D dose-dependently suppressed the ANO1 activation-mediated decrease in fluorescence of yellow fluorescent protein; however, it did not affect the adenosine triphosphate-induced increase in the intracellular calcium concentration or forskolin-induced cystic fibrosis transmembrane conductance regulator activity. Specifically, schisandrathera D gradually decreased the levels of ANO1 protein and significantly reduced the cell viability in ANO1-expressing cells when compared to those in ANO1-knockout cells. These effects could be attributed to the fact that schisandrathera D displayed better binding capacity to ANO1 protein than the previously known ANO1 inhibitor, Ani9. Finally, schisandrathera D increased the levels of caspase-3 and cleaved poly [ADP-ribose] polymerase 1, thereby indicating that its anticancer effect is mediated through apoptosis. Thus, this study highlights that schisandrathera D, which reduces ANO1 protein levels, has apoptosis-mediated anticancer effects in prostate and oral cancers, and thus, can be further developed into an anticancer agent.